The Big Yawning: Pathological Yawning as a Symptom of Neuromyelitis Optica Spectrum Disorders - Veronika Spahlinger; Annette Niessen; Sebastian Rauer; Stefan Krämer; Matthias Reinhard (Case Reports in Neurological Medicine)
Pathological yawning is rarely observed in cerebral or spinal diseases. A 67-year-old woman was admitted with a seven-day progressive hemisyndrome with left-sided limb ataxia and hypesthesia. The patient yawned with a high frequency, partially in salve-like episodes. MRI showed a cervical myelitis over more than three vertebral segments up to the lower medulla and Aquaporin-4-antibodies were positive (diagnostic criteria for a Neuromyelitis optica spectrum disorder were fulfilled). Under treatment with methylprednisolone, followed by plasmapheresis and immunoadsorption, clinical symptoms were regressive and the frequency of yawning completely normalized. When observing pathological yawning, even in the absence of other cerebral or brainstem symptoms, one should be aware of NMOSD as a possible cause.